P636 The natural history of COVID-19 in patients with IBD: A nationwide study by the Hellenic Society for the Study of IBD. (27th May 2021) - Bamias, G; Kokkotis, G; Christodoulou, D; Delis, V; Gatopoulou, A; Giouleme, O; Kalantzis, C; Kapsoritakis, A; Karatzas, P; Karmiris, K; Katsanos, K; Kevrekidou, P; et al.
Abstract: Background: COVID-19 has evolved into a global health crisis, variably affecting the management of patients with chronic illnesses. Patients with inflammatory bowel disease (IBD) may represent a vulnerable population due to the frequent administration of immune-modifying treatments. Methods: We aimed to depict the natural history of COVID-19 infection in Greek patients with IBD at a nationwide level via the unbiased reporting of all cases that were registered during the first and second waves of the pandemic. Following a national call from the Hellenic Society for the study of IBD, we enrolled all IBD patients with established diagnosis of COVID-19. Clinical and epidemiological data, including COVID-19 modifying factors and IBD-associated therapies were analysed against adverse outcomes (hospitalization, ICU admission, and death). Results: We identified 80 patients with IBD who were diagnosed with COVID-19 during the study period (male:65%; median age=44 [IQR=26] years; CD:62.5%). Adverse outcomes were reported in 16 patients (20%), including 3 ICU admissions (3.75%) and 2 deaths (2.5%). Negative prognostic factors for adverse outcomes included age, Body Mass Index, and hypertension, as well as dyspnoea, fatigue and abdominal pain at presentation. In contrast, treatment with biologics, in particular anti-TNF agents, exerted a protective effect against an unfavorable course COVID-19. Patients on subcutaneous biologics were more likely to halt treatment due to the infection as compared to those on intravenous medications. Conclusion: Patients with IBD who developed COVID-19 had a benign course with adverse outcomes being scarce. Treatment with biologics had a beneficial effect, supporting the continuation of therapy during the pandemic.